2016
DOI: 10.1631/jzus.b1500247
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional protein: cardiac ankyrin repeat protein

Abstract: Cardiac ankyrin repeat protein (CARP) not only serves as an important component of muscle sarcomere in the cytoplasm, but also acts as a transcription co-factor in the nucleus. Previous studies have demonstrated that CARP is up-regulated in some cardiovascular disorders and muscle diseases; however, its role in these diseases remains controversial now. In this review, we will discuss the continued progress in the research related to CARP, including its discovery, structure, and the role it plays in cardiac dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Consequently, sarcomere disarray and loss of myofilaments leads to abnormal cardiac contractility. 69,70 It is suggested that GATA-4 and CARP co-dependency is needed for sarcomere organization and functioning, while dox overts their association during myofibrillar disarray and hypertrophy. 71 Combining the above stated facts, it can be understood that DOX interrupts cardiac contractile and pumping machinery through sarcomeric genes such as actin, TnI, MLC2, and CK-M, without affecting skeletal myocytes.…”
Section: Dox and The Cardiac Sarcomere Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, sarcomere disarray and loss of myofilaments leads to abnormal cardiac contractility. 69,70 It is suggested that GATA-4 and CARP co-dependency is needed for sarcomere organization and functioning, while dox overts their association during myofibrillar disarray and hypertrophy. 71 Combining the above stated facts, it can be understood that DOX interrupts cardiac contractile and pumping machinery through sarcomeric genes such as actin, TnI, MLC2, and CK-M, without affecting skeletal myocytes.…”
Section: Dox and The Cardiac Sarcomere Proteinsmentioning
confidence: 99%
“…It is observed that the level and activity of CARP is suppressed by DOX, which is connected to dilated and hypertrophic cardiomyopathy and skeletal muscle myopathies. Consequently, sarcomere disarray and loss of myofilaments leads to abnormal cardiac contractility 69,70 . It is suggested that GATA‐4 and CARP co‐dependency is needed for sarcomere organization and functioning, while dox overts their association during myofibrillar disarray and hypertrophy 71 …”
Section: Effects Of Dox On the Cardiac Regimementioning
confidence: 99%
“…Representative genes from the top 6 most significantly differentially regulated signaling pathways activated by SV serum-treatment including ceramide, p38 MAPK, PLC, cardiac hypertrophy, actin cytoskeleton, and oxidative stress response signaling (Figure S2) were chosen for further analysis. Confirmatory analysis by RT-qPCR was performed on human RV tissue for representative genes in each pathway, including (1) ceramide kinase CERK 31 , (2) cyclic AMP-responsive transcription factor CREB5 32,33 , (3) non-receptor tyrosine kinase FYN 34,35 , (4) cardiac ankyrin repeat domain ANKRD1 36,37 , (5) α-actinin isoform ACTN2 38,39 , and (6) transcription factor MAFK 40 . RT-qPCR revealed that these representative genes were significantly upregulated in SV RV relative to NF control RV, consistent with the SV-sera NRVM treatment findings (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…[ 18 ] Moreover, its interference on the iron metabolism (Fe 3+ ) [ 34 ] and in the cardiac synthesis of ankyrin repeat protein increases reactive oxygen species production and compromises the myocyte survival and cellular transcription, respectively. [ 35 ] In a prospective study, an increase in proapoptotic proteins (sFas and sTRAIL) was detected 1 year after the end of the chemotherapy treatment for breast cancer, evidencing the chronic residual effects of this treatment. [ 36 ] However, the authors did not find a correlation between these biomarkers levels with the predictive risk of cardiac dysfunction or with the subclinical alterations in the left ventricle ejection fraction and NT-proBNP levels (a biomarker of heart failure), also detected in the study.…”
Section: Discussionmentioning
confidence: 99%